Insights from the Genome Sequence of Acidovorax citrulli M6, a Group I Strain of the Causal Agent of Bacterial Fruit Blotch of Cucurbits - Eckshtain-Levi, Noam; Shkedy, Dafna; Gershovits, Michael; Da Silva, Gustavo M.; Tamir-Ariel, Dafna; Walcott, Ron; Pupko, Tal; Burdman, Saul (Frontiers in Microbiology, 2016)
Acidovorax citrulli is a seedborne bacterium that causes bacterial fruit blotch of cucurbit plants including watermelon and melon. A. citrulli strains can be divided into two major groups based on their host preference, DNA fingerprint analyses and biochemical properties. Group I strains have been generally isolated from non-watermelon cucurbits, while group II strains are closely associated with watermelon. In the present study, we report the genome sequence of M6, a group I model A. citrulli strain, isolated from melon. We used comparative genome analysis to investigate differences between the genome of strain M6 and the genome of the group II model strain AAC00-1. The draft genome sequence of A. citrulli M6 harbors 139 contigs, with an overall approximate size of 4.85 Mb. The genome of M6 is 500 Kb shorter than that of strain AAC00-1. Comparative analysis revealed that this size difference is mainly explained by eight fragments, ranging from 35 to 120 Kb and distributed throughout the AAC00-1 genome, which are absent in the M6 genome. In agreement with this finding, while AAC00-1 was found to possess 532 open reading frames (ORFs) that are absent in strain M6, only 123 ORFs in M6 were absent in AAC00-1. Most of these M6 ORFs are hypothetical proteins and most of them were also detected in two group I strains that were recently sequenced, tw6 and pslb65. Further analyses by PCR assays and coverage analyses with other A. citrulli strains support the notion that some of these fragments or significant portions of them are discriminative between group I and II strains of A. citrulli. Moreover, GC content, effective number of codon values and cluster of orthologs’ analyses indicate that these fragments were introduced into group II strains by horizontal gene transfer events. Our study reports the genome sequence of a model group I strain of A. citrulli, one of the most important pathogens of cucurbits. It also provides the first comprehensive comparison at the genomic level between the two major groups of strains of this pathogen.